(untitled) (Al-Qamar, 2025)
This study presents a comprehensive exploration of the Seerah of the Holy Prophet Muhammad ﷺ, underscoring its intellectual, moral, spiritual, and civilizational significance. It argues that the Prophet’s ﷺ life is not confined to a historical narrative but constitutes a universal paradigm that addresses every sphere of human existence, including ethics, spirituality, social justice, governance, and cultural development. The article highlights that the Seerah embodies timeless principles of justice, compassion, tolerance, and wisdom, offering enduring solutions to modern challenges such as moral decline, social injustice, extremism, and global disharmony. Through an analytical study of key events and teachings, the research illustrates how the Prophetic model provides guidance for building a balanced, harmonious, and progressive society. The paper concludes that a profound engagement with Seerat-un-Nabi ﷺ is essential not only for the moral and spiritual uplift of Muslims but also for the broader well-being of humanity, as it offers a complete framework for establishing peace, justice, and civilizational harmony across time and space.